Analysis of Public Building Façade on Gatot Subroto Street, Bandar Lampung City, Indonesia - Ai Siti Munawaroh; Deri Ade Nugroho (Program Studi Arsitektur Fakultas Sains dan Teknik (F-INTEN), 2023)
The facade is the main element of the outside of the building. Building facades are also a special part of architectural work. This is because this element is the first part to be appreciated by every connoisseur of architecture. Therefore, it is important to examine the facades of buildings, especially on the main roads of the city of Bandar Lampung. This study aims to examine the facades of buildings on Jl. Gatot Subroto Bandar Lampung which is the main road section. On that road, two luxury hotels are the center of various activities on a local, national and international scale. This research method uses qualitative methods by collecting data, literature studies, field observations, and documentation. There are two data collection methods, namely primary data obtained directly from the field and secondary data obtained from various related sources. The research results obtained are the typology of facades in public buildings on Jl. Gatot Subroto Bandar Lampung, Indonesia, is mostly rectangular and uses Aluminum Composite Panel (ACP) walls and Buffer Systems and Twin Face Systems.